Acute effect of high-intensity interval exercise on vascular endothelial function and possible mechanisms of wall shear stress in young obese males - Shi, Wenxia; Liu, Haibin; Cao, Ling; He, Yufeng; Su, Pei; Chen, Jiangang; Wang, Mengyue; Li, Xulong; Bai, Shuang; Tang, Donghui (Frontiers in Physiology, 2022)
Objective: To investigate the mechanisms of wall shear stress (WSS) responsible for the effects of high-intensity interval exercise (HIIE) on vascular endothelial function in young obese males. Methods: A within-subject study design was used. We examined the response of the reactive hyperemia index (RHI) to acute HIIE in young obese males (n=20, age=20.38±1.40 years, body mass index [BMI] =31.22±3.57, body fat percentage [BF (%)]=31.76±3.57). WSS was manipulated using 100 mmHg, 80 mmHg, or 60 mmHg cuff inflation during the HIIE to determine the proper inflation capable of maintaining WSS near baseline levels. One-way repeated measures analysis of variance and LSD post hoc tests were performed to compare changes in WSS and vascular endothelial function at baseline HIIE and following HIIE using different cuff inflations. Results: There were no significant differences in RHI and WSS between the three cuff inflation values (P>0.05). WSS was significantly higher in obese male individuals after HIIE and HIIE with 100 mmHg cuff inflation (P=0.018, P=0.005) than that at baseline, with no significant differences observed comparing HIIE and HIIE with 100 mmHg inflation (P=0.23). The RHI after HIIE was significantly higher (P=0.012) than that at baseline, while no significant differences were detected after HIIE at 100 mmHg (P=0.91). The RHI was significantly lower after HIIE with 100 mmHg than that after HIIE (P=0.007). WSS (P=0.004) and RHI (P=0.017) were significantly higher after HIIE than that at baseline, while no significant differences were observed after HIIE with either 80 mmHg or 60 mmHg cuff inflation (baseline vs. HIIE+80 mmHg: WSS: P=0.33, RHI: P=0.38; baseline vs. HIIE+60 mmHg: WSS: P=0.58, RHI: P=0.45). WSS was similar to HIIE, after HIIE with either 80 mmHg or 60 mmHg inflation (P=0.36, P=0.40). However, RHI was significantly higher for HIIE than for HIIE with both 80 mmHg and 60 mmHg inflation (P=0.011, P=0.006). Conclusions: HIIE could significantly improve WSS and vascular endothelial function. HIIE intervention with 60 or 80 mmHg inflation might enhance WSS near the baseline level. HIIE-induced acute changes in WSS may provide the primary physiological stimulus for vascular endothelial adaptation to HIIE in young obese males.